The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1200/jgo.19.00179
|View full text |Cite
|
Sign up to set email alerts
|

Does Interim PET Scan After 2 Cycles of ABVD Predict Outcome in Hodgkin Lymphoma? Real-World Evidence

Abstract: PURPOSE Escalated BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone) improves overall survival (OS) in patients with Hodgkin lymphoma (HL) relative to ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) therapy. However, the associated higher cost and toxicity discourage clinicians from prescribing it. Identifying high-risk patients and administering escalated BEACOPP remains an effective strategy. We assessed the significance of interim positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In comparison with adult HL patients, the studies on iPET2 response adapted treatment modification in pHL are sparse. 26,[31][32][33][34] In our study, patients not achieving CR in the iPET2 scan had five times increased risk of an adverse outcome when compared with patients achieving CR. Results from several studies on the role of iPET scan in the management of pHL are varied and conflicting.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In comparison with adult HL patients, the studies on iPET2 response adapted treatment modification in pHL are sparse. 26,[31][32][33][34] In our study, patients not achieving CR in the iPET2 scan had five times increased risk of an adverse outcome when compared with patients achieving CR. Results from several studies on the role of iPET scan in the management of pHL are varied and conflicting.…”
Section: Discussionmentioning
confidence: 48%
“…[26][27][28][29][30] In comparison with adult HL patients, the studies on interim PET scan after two cycles (iPET2) response adapted treatment modification in children are sparse. 26,[31][32][33][34] This study was conducted to ascertain the outcomes of children with HL treated with ABVD chemotherapy and to analyze various factors predicting the outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Girinsky et al [166], historic radiation fields encompassed significant portions of healthy tissue, whereas modern radiation therapy techniques are able to limit radiation fields to focus on tumours identified by pre-treatment PET-CT, decreasing toxicities without compromising oncologic outcomes. For certain cancers, PET-CT is also utilised to evaluate treatment response after administration of chemotherapy [167]. This opens a new perspective for glucose-targeted drug therapies [168].…”
Section: The Warburg Effect From a Clinical Perspective: Status Quomentioning
confidence: 99%
“…[11] Recent reports from a multicenter analysis have shown that RAT can be safely practiced in the Indian conditions. [20] Prasanth Ganesan…”
Section: Approach May Be An Optimal Approach For Indian Patients Who Have Access To Positron Emission Tomography-computed Tomographymentioning
confidence: 99%